2017
DOI: 10.24327/ijrsr.2017.0804.0137
|View full text |Cite
|
Sign up to set email alerts
|

Anemia prevalence in adolescent school going girls

Abstract: ARTICLE INFO ABSTRACT Aim:The aim was to find out the prevalence of anemia in the adolescent girls in the schools of rural area and the influence of micronutrients on different grades of anemia. Materials and methods: It was a cross-sectionals study. 501 school going adolescent girls were enrolled for the study after informed consent. Data for demographic profile were collected, followed by blood sample collection for analysis of hemoglobin, iron profile and vitamin B12. Results: Prevalence of anemia was 40.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…(13) The current study reported that the most prevalent disability was Down's syndrome, Also, this is in line with Sharma and Mishra, (20) study who reported that both The present study found that the mean Hb level was statistically lower in underweight females in the age group (≥11 -14 years old). Similar results reported by Puja et al, (21) who found a significant distribution of anemia in low BMI school in Indian adolescent females which may be attributed to malnutrition and the onset of menstrual periods in girls are related to iron deficiency anemia during adolescence.…”
Section: Discussionsupporting
confidence: 88%
“…(13) The current study reported that the most prevalent disability was Down's syndrome, Also, this is in line with Sharma and Mishra, (20) study who reported that both The present study found that the mean Hb level was statistically lower in underweight females in the age group (≥11 -14 years old). Similar results reported by Puja et al, (21) who found a significant distribution of anemia in low BMI school in Indian adolescent females which may be attributed to malnutrition and the onset of menstrual periods in girls are related to iron deficiency anemia during adolescence.…”
Section: Discussionsupporting
confidence: 88%
“…In the study conducted by Thomas et al (2015), when anaemic adolescents were assessed for nutritional status by assessing BMI, it was found that 54% were in the normal range of BMI, 27.5% were very underweight, 17.5 % were underweight, and only 1% were overweight. Dhuppar et al (2017) studied 501 school going adolescent girls out of the 204 girls were anaemic, among them 125 had BMI below 18.5, 74 had BMI between 18.5-25 and 5 had BMI between 25.1-29.…”
Section: Bmi Categories Of Study Participantsmentioning
confidence: 99%